DIPPING PROFILE, NIGHTTIME SYSTOLIC BLOOD PRESSURE AND VASCULAR DAMAGE IN PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2018) - Anyfanti, P.; Gkaliagkousi, E.; Lazaridis, A.; Triantafyllou, A.; Koletsos, N.; Dolgyras, P.; Triantafyllou, G.; Chatzimichailidou, S.; Aslanidis, S.; Douma, S.
Abstract : Objective: Both increased nighttime systolic blood pressure (SBP) and a non-dipping pattern are predictors of adverse cardiovascular outcomes. We investigated dipping profile and nighttime SBP in relationship with subclinical vascular damage in patients with rheumatoid arthritis (RA), a disease characterized by excess cardiovascular risk. Design and method: Patients with RA and non-RA individuals underwent 24-hour ambulatory blood pressure monitoring. Carotid-femoral pulse wave velocity (PWV) was assessed with applanation tonometry as a measure of central arterial stiffness. Carotid atherosclerosis was evaluated from carotid ultrasound by measurement of carotid intima-media thickness (cIMT). Peripheral vascular resistance was estimated from impedance cardiography. Disease-related characteristics were addressed, including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), disease duration and activity, and pain. Results: RA patients (n = 91) exhibited a higher prevalence of non-dipping pattern (64.8 vs 28.0 %, p < 0.001), elevated nighttime SBP (112.6 ± 12.8 vs 105.8 ± 9.7 mmHg, p = 0.001) and a lower degree of dipping (6.5 ± 7.4 vs 13.0 ± 5.6 %, p < 0.001), compared to non-RA individuals (n = 50), whereas both office and daytime SBP did not differ. In the RA group, dipping (%) was inversely associated with PWV (r = –0.218, p = 0.045). Nighttime SBP strongly correlated with all vascular indices, including PWV (r = 0.493, p < 0.001), cIMT (r = 0.407, p < 0.001) and systemic vascular resistance index (r = 0.383, p < 0.001). In addition, nighttime SBP increased with increasing ESR (r = 0.213, p = 0.046), CRP (r = 0.245, p = 0.022), intensity of pain over the past 24-hour hours (r = 0.255, p = 0.042) and disease duration (r = 0.246, p = 0.027). The combination of a non-dipping profile with high nighttime SBP was accompanied by the highest (p = 0.019) PWV (10.0 ± 2.5 m/s), compared to both non-dippers with normal nighttime SBP (7.8 ± 2.1 m/s, p = 0.003) and dippers (8.1 ± 1.9 m/s). In the multivariate analysis for dipping, ESR was identified as an independent predictor (beta = –0.234, p = 0.037), and the same was observed in the multivariate analysis for nighttime SBP (beta = 0.201, p = 0.019). Conclusions: Patients with RA exhibit high prevalence of blunted dipping due to elevated nighttime SBP. Inflammation appears to mediate the observed associations of nighttime SBP and dipping with markers of central and peripheral vascular damage. The combination of a non-dipping profile with abnormal nighttime SBP is accompanied by pronounced subclinical vascular impairment.